Justicia popular: Sobre la dimensión judicial del primer constitucionalismo iberoamericano - Slemian, Andréa; Garriga, Carlos (Jahrbuch für Geschichte Lateinamerikas, 2018)
This article proposes that one of the most significant features of justice in the first Latin American constitutionalism, that developed in response to the crisis of the Iberian monarchies, is its popular dimension. This popular dimension was conditioned both by the difficulties of organizing a learned justice and by a strong distrust of the professional judges. Within the framework of a shared and highly determining legal tradition, and alongside the invocations of the law’s centrality, different forms of lay participation were constitutionally articulated in the administration of justice – either to judicially determine the law, either to elect, or to control who judicially determines the law. After rebuilding the normative discourse about justice and its institutions in this constitutionalism, we will pursue here the traces of such popular justice.
Keywords: Judicial Institutions; Nineteenth Century; Jury; Justices of the Peace; Elected Justice